The blessings of liberty human rights and religious freedom in the western legal tradition - Witte, John 1959- (Cambridge University Press, 2022)
Leading legal scholar John Witte, Jr. explores the role religion played in the development of rights in the Western legal tradition and traces the complex interplay between human rights and religious freedom norms in modern domestic and international law. He examines how US courts are moving towards greater religious freedom, while recent decisions of the pan-European courts in Strasbourg and Luxembourg have harmed new religious minorities and threatened old religious traditions in Europe. Witte argues that the robust promotion and protection of religious freedom is the best way to protect many other fundamental rights today, even though religious freedom and other fundamental rights sometimes clash and need judicious balancing. He also responds to various modern critics who see human rights as a betrayal of Christianity and religious freedom as a betrayal of human rights
Title from publisher's bibliographic system (viewed on 28 Oct 2021)
Christian contributions to the development of rights and liberties in the Western legal tradition -- Magna Cartas old and new : rights and liberties in the Anglo-American common law -- Natural law and natural rights in the early Protestant tradition -- "A most mild and equitable establishment of religion" : religious freedom in Massachusetts, 1780-1833 -- Historical foundations and enduring fundamentals of American religious freedom -- Balancing the guarantees of no establishment and free exercise of religion in American education -- Tax exemption of religious property : historical anomaly or valid constitutional practice? -- Faith in Strasbourg? religious freedom in the European Court of Human Rights -- Meet the new boss of religious freedom : the new cases of the Court of Justice of the European Union -- Concluding reflections : toward a Christian defense of human rights and religious freedom today
Keywords: European Court of Human Rights; Magna Carta / Influence; Geschichte; Human rights; Freedom of religion / European Union countries; Freedom of religion / United States / History; Christianity and law; Christianity / Influence; Civil rights / Religious aspects / Christianity; Religionsfreiheit; Menschenrecht